Rol de la proteína sparc en la biología adenoviral orientada al uso terapéutico - Rivas Baquero, Elvia Carolina (2015)
Today, great strides have been made in the field of gene therapy for cancer treatment, and in this field, the use of oncolytic viruses is presented with promising advances, since they not only have a preferential tropism for transformed cells but also they mediate cytotoxic processes in infected cells, without harming normal cells. Within oncolytic viruses are conditionally replicative adenovirus (CRAds) based in adenovirus that infect humans. In our laboratory was built a CRAd whose replication is driven by a chimeric promoter with a fragment of the SPARC promoter, hypoxia response elements and inflammation, besides having a chimera fiber 5/3. This virus was called adenovirus 5/3 NHS. In the search for new strategies for the delivery of CRAds to the tumor, mesenchymal cells were used (MSCs) pre-infected with Ad 5/3 NHS as a means of transport for the same. It was observed that by infecting these cells, both in the presence of conditioned medium of tumor cells that express the SPARC protein, as in the presence of purified protein SPARC, the infection turn out to be more efficient, demonstrating an increase in lysis at lower multiplicity of infection (MOI).\nStarting from this premise, this work aimed to assess whether the effect observed in MCSs reproduced in tumor cells. This three strategies were used: Infections in the presence of conditioned medium from cells secreting SPARC, infection in the presence of the purified protein SPARC and infections in cells expressing or not SPARC using 3 viruses: Ad5/3 Luciferase as a non-replicative control, Ad5/3 WT as positive control and the Ad5/3 NHS generated in our laboratory. The strategy that involve an infection in the presence of conditioned media do not represent an efficient test for evaluating the effect of SPARC, since it inhibited cell growth. SPARC expression and exogenously added protein promotes adenovirus mediated lysis. However, studies of expression of CAR, CD46 and Desmoglein-2 adenoviral receptors and virus entry by quantification of copies of E4 gene and immunofluorescence, suggest that the mechanism used by SPARC is unrelated to adenoviral cycle stages related to receptor binding and virus entry.